2023
DOI: 10.1039/d2tc04713f
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent organic molecular frameworks from tetraphenylethylene-based building blocks

Abstract: Organic molecular framework materials are an emerging type of porous materials formed by discrete molecules through weak supramolecular interactions. They have unique flexibility, solution processability and potential applications in gas...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…The luminescence in solution is not turned on when the measurement is performed at 77 K, which discard the conformational flexibility from being the cause of the low quantum yield. As expected, it exhibits a typical blue fluorescence with a maximum at 490 nm in the solid state with an average lifetime of 1.8 ns, in the range of known TPE derivatives [7g] . Surprisingly, its absolute emission quantum yield was estimated at 1 %, which is considerably lower than related analogs previously described [22] .…”
Section: Resultssupporting
confidence: 66%
“…The luminescence in solution is not turned on when the measurement is performed at 77 K, which discard the conformational flexibility from being the cause of the low quantum yield. As expected, it exhibits a typical blue fluorescence with a maximum at 490 nm in the solid state with an average lifetime of 1.8 ns, in the range of known TPE derivatives [7g] . Surprisingly, its absolute emission quantum yield was estimated at 1 %, which is considerably lower than related analogs previously described [22] .…”
Section: Resultssupporting
confidence: 66%
“…Early studies on TPE mainly focused on the excited-state dynamics associated with the conformation of the TPE molecule in solutions. Its popularity began in 2006 when Tang et al reported the aggregation-induced emission (AIE) of TPE derivatives . Since then, the AIE phenomenon of TPE derivatives has become one of the most important topics in chemistry, materials science, and beyond, as summarized in many reviews. Following such extensive fundamental research, work is now focused on the development of TPE-based fluorescent materials with commercial prospects.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Tetraphenylethylene (TPE) is a star molecule of AIE materials, widely used due to its simple synthesis, modification, and unusual luminescence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] A series of eightshaped double macrocycles can be formed by connecting the benzene rings of TPE in pairs (Scheme 1). These structures have received great attention, leading to a series of studies on the AIE mechanism, ion recognition, and multicolor luminescence.…”
Section: Introductionmentioning
confidence: 99%